Parasexuality of Candida Species - Mishra, Abhishek; Forche, Anja; Anderson, Matthew Z. (Frontiers in Cellular and Infection Microbiology, 2021)
While most fungi have the ability to reproduce sexually, multiple independent lineages have lost meiosis and developed parasexual cycles in its place. Emergence of parasexual cycles is particularly prominent in medically relevant fungi from the CUG paraphyletic group of Candida species. Since the discovery of parasex in C. albicans roughly two decades ago, it has served as the model for Candida species. Importantly, parasex in C. albicans retains hallmarks of meiosis including genetic recombination and chromosome segregation, making it a potential driver of genetic diversity. Furthermore, key meiotic genes play similar roles in C. albicans parasex and highlights parallels between these processes. Yet, the evolutionary role of parasex in Candida adaptation and the extent of resulting genotypic and phenotypic diversity remain as key knowledge gaps in this facultative reproductive program. Here, we present our current understanding of parasex, the mechanisms governing its regulation, and its relevance to Candida biology.